Review and conservation priority of medicinal plants in riverside communities in the Amazon estuary, Pará, Brazil - Marques, Wendel Patrick Gomes; Costa Lima, Pedro Glécio; Coelho-Ferreira, Márlia Regina (Ethnobotany Research and Applications, 2025)
Background: The use of medicinal plants (MP) is a very common practice among Amazonian communities. Traditional knowledge is a good source of information for planning strategies for the conservation of MP. Here, we identify medicinal species to be prioritized for conservation in communities of riverside dwellers along the Pará River and Marajó Bay, in the Amazon estuary. Methods: We searched the scientific literature of the last 35 years (1985 to 2020) on the use and knowledge of these resources and aspects related to medicinal versatility, forms of collection, parts used, anthropic pressure and origin (cultivation/extractivism) to estimate the indices of Relative Importance (RI), Sensitivity (SI) and Importance Value (IVI) in order to evaluate the priority species for conservation actions. Results: A total of 343 MP was recorded, distributed in 84 botanical families, with Fabaceae standing out. Socratea exorrhiza (paxiúba), a typical floodplain species, stood out as the most vulnerable to anthropogenic collection and pressure (SI = 0.99). Carapa guianensis (castanha-do-Pará/Brazil nut) stood out with great versatility regarding its uses (RI = 1.88) and higher importance value (IVI = 2.85). Conclusions: Another 33 species can be considered high priority for conservation in the communities surveyed. Recommendations were suggested for local strategies for sustainable use and management. Keywords: Ethnobotany, Medicinal species, Brazilian Amazon, Amazonian Floodplain Forest, Local Knowledge. Resumo Contexto: O uso de plantas medicinais (PM) é uma prática muito comum entre as comunidades amazônicas. O conhecimento tradicional é uma boa fonte de informação para o planejamento de estratégias de conservação de MP. Aqui, identificamos espécies medicinais a serem priorizadas para conservação em comunidades de moradores ribeirinhos ao longo do Rio Pará e da Baía de Marajó, no estuário do Amazonas. Métodos: Foi realizada busca na literatura científica dos últimos 35 anos (1985 a 2020) sobre o uso e conhecimento desses recursos e aspectos relacionados à versatilidade medicinal, formas de coleta, partes utilizadas, pressão antrópica e origem (cultivo/extrativismo) para estimar os índices de Importância Relativa (IR), Sensibilidade (IS) e Valor de Importância (IVI) para avaliar as espécies prioritárias para ações de conservação. Resultados: Foram registrados 343 PM, distribuídos em 84 famílias botânicas, com destaque para Fabaceae. Socratea exorrhiza (paxiúba), espécie típica de várzea, destacou-se como a mais vulnerável à coleta e pressão antrópica (IS = 0,99). Carapa guianensis (castanha-do-Pará/castanha-do-brasil) destacou-se pela grande versatilidade quanto aos usos (RI = 1,88) e maior valor de importância (IVI = 2,85). Conclusões: Outras 33 espécies podem ser consideradas de alta prioridade para conservação nas comunidades pesquisadas. Foram sugeridas recomendações para estratégias locais de uso e gestão sustentáveis. Palavras-chave: Etnobotânica, Espécies medicinais, Amazônia brasileira, Floresta de várzea amazônica, Conhecimento local.